Software Development For Optimal Portfolio Selection Using The Markowitz Method - Restuningdiah, Nurika; Makaryanawati, Makaryanawati; Azzardina, Aulia (AIBPM Publisher, 2023)
Investors could invest their funds in a collection of financial assets (portfolio). The optimal combination of the portfolio will optimal the return. The purpose of this study is the development of Optimal Portfolio Software to support investment decisions, using the Markowitz model. The software will support the Investment Management course in the classroom. The development process consists of Analysis, Design, and Development Stages. The output of this research is Markowitz Methods Software, that validated by expert judgment.Keywords:, Investment Management Learning, Investment Decision Making, Markowitz Methods Software, Optimal Portfolio, Portfolio.